Impact of Saccharomyces cerevisiae Fermentation Product on Feed Intake Parameters, Lactation Performance, and Metabolism of Transition Dairy Cattle - K. Olagaray; S. E. Sivinski; B. A. Saylor; L. K. Mamedova; J. A. Sauls; I. Yoon; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2018)
ASaccharomyces cerevisiaefermentation product (NutriTek; Diamond V, Cedar Rapids, IA) was fed from 29 ± 5 days before calving and through 42 days in milk (DIM) to evaluate the effects on feed intake parameters, milk production, and metabolism. Treatments were control (n= 30) or 18 g/d NutriTek (NT,n= 34) provided as total mixed rations. Cows were individually fed 3×/day prepartum and 2×/day postpartum. Cows were milked 2×/day with samples taken 2×/week for composition analysis. Body weight (BW) was measured at enrollment (day -29 ± 5), day 0, and day 42 relative to calving, and body condition was scored weekly. Blood samples were collected during weeks -4, -2, 1, 2, and 5 relative to calving for biomarkers of metabolism and inflammation. To evaluate adaptive immunity, cows were challenged with a subcutaneous injection of ovalbumin (egg protein) and immune response was determined by serum concentrations of anti-ovalbumin immunoglobulin G (IgG) on days 7, 21, 28, and 35 of lactation. Overall dry matter intake, BW, body condition score, and milk yield were not different between treatments. NutriTek did alter feeding behavior by increasing the number of meals consumed with less time between those meals. Milk fat concentration increased with NT during weeks 4 and 5 of lactation, which contributed to an increase in fat yield during those weeks. There were tendencies for greater milk lactose yield in control cows and greater milk urea nitrogen concentration in NT, but no treatment differences for milk protein concentration or somatic cell count. Assuming equal digestibility, energy balance was more negative for NT during weeks 4 and 5, mirroring the increase in milk fat during that time. Energy density of diets calculated from observed ECM yield and BW change did not differ by treatment. Plasma concentrations of free fatty acids, β-hydroxybutyrate (BHB), glucose, insulin, and the inflammation marker haptoglobin did not differ between treatments. NutriTek increased the incidence of subclinical ketosis (12 vs. 38%, diagnosed by urine ketones). There was no overall treatment effect for immune response to vaccination; however, a treatment × parity interaction indicated greater antibody concentration in primiparous cows supplemented with NT. A partial budget analysis accounting for milk income, feed cost, and expense associated with ketosis treatment indicated an additional 0.35 daily profit per cow for NT vs. control. In conclusion, NT supplementation during the transition period altered feeding behavior and milk fat concentration and ultimately appeared profitable in this scenario, despite the increased incidence of subclinical ketosis and a lack of response in early lactation milk yield.
Keywords: Saccharomyces cerevisiae fermentation product; NutriTek; transition cow